The color changes on varnish layers after accelerated aging through the hot and cold-check test - Budakci, M; Korkut, D S; Esen, R (African journal of biotechnology, 2010)
The purpose of this paper is to determine the color changes of cellulosic, polyurethane and acrylic varnish layers which were applied on the surfaces of Scots pine (Pinus sylvestris L), Eastern beech (Fagus orientalis L.) and sessile oak (Quercus petraea L.) wood material after accelerated aging effects through the hot and cold-check test. For this purpose, test samples were firstly kept at 50 c 5C temperature for 1 h, and then conditioned for 1 h in a conditioning room, later moved to -20 c 2C temperature keeping for 1 h according to ASTM D1211-97 standard. These processes were accepted as 1 cycle and tests were continued to 20 cycles. Then the color changes were determined by using Minolta CR-231 device of tristimulus colorimeter according to ASTM D2244-07e1 standard. It was found that most color change was determined in cellulosic, polyurethane and acrylic varnish layers on the surfaces of Scots pine (Pinus sylvestris L.), Eastern beech (F. orientalis L.) and sessile oak (Q. petraea L.) wood material. The endurance of the protective coating (such as paint and varnish) to external effects is limited and the lifetime of the coating is determined by the type and the severity of the effects to which it is exposed. The effect of a color change on varnish layers can determine the usefulness of the varnish. It is conjectured that especially for the manufacturers and consumers in the furniture and decoration sector, the data obtained in this study will contribute to the making up of deficiencies in the understanding of the subject.